Integration of Digital Technologies into Business Processes: Companies in Slovak Republic in the Context of Global Development and the Current State in the European Union - Anita ROMANOVÁ; Diana BEDNARČÍKOVÁ (Communications of International Proceedings, 2021)
An integral part of Industry 4.0 are digital technologies, also called Industry 4.0 technologies, whose integration into business processes leads to digitization and the company has a chance to become digital and later intelligent. Digital technologies have a broad use in almost all industries and bring many benefits to businesses. The aim of the scientific article is to review the integration of digital technologies into business activities in companies in the Slovak Republic and to comparison with the situation in companies in the European Union and with other selected countries around the world. The article focuses on the general definition of digitization, digitalization, digital technologies and digital transformation of enterprises, comparison of the use of digitization and Industry 4.0 technologies in business processes based on available statistical data and other published research studies.
Keywords: Industry 4.0; Information Technology; Digitalization; Digitization.